Correlation of Sprouty1 and Jagged1 With Aggressive Prostate Cancer Cells With Different Sensitivities to Androgen Deprivation. Issue 9 (September 2014) - Terada, Naoki; Shiraishi, Takumi; Zeng, Yu; Aw‐Yong, Koh‐Meng; Mooney, Steven M.; Liu, Zhi; Takahashi, Sayuri; Luo, Jun; Lupold, Shawn E.; Kulkarni, Prakash; Getzenberg, Robert H.
ABSTRACT Prostate cancer is a heterogeneous disease and thus, it is important to understand whether among the heterogeneous collection of cell types, androgen‐deprivation insensitive cells exist prior to hormonal manipulation. We established several LNCaP subclones with distinct insensitivities to androgen deprivation from a parental LNCaP cell line. In the resulting clones, the sensitivity to androgen‐deprivation negatively correlated with their PSA expression levels. In two of these clones, an androgen insensitive clone, LNCaP‐cl1, and an androgen sensitive clone, LNCaP‐cl5, the DNA copy number differed significantly, indicating that these clones contain genetically distinct cells. LNCaP‐cl1 had higher PSA expression but lower invasiveness and tumor growth potential than LNCaP‐cl5. The expression levels of two genes that are known to be regulated by miR‐21, an androgen‐regulated microRNA, Sprouty1 (SPRY1) and Jagged1 (JAG1) were significantly lower in LNCaP‐cl1 than in LNCaP‐cl5. Knocking down SPRY1 in LNCaP cells enhanced PSA expression and cell proliferation. JAG1 administration in LNCaP cells enhanced cell invasion and JAG1 knockdown in PC3 cells suppressed cell invasion and tumor formation. These results indicated that the expression differences in SPRY1 and JAG1 may contribute to the phenotypic differences between the LNCaP‐cl1 and LNCaP‐cl5 clones. In tissue samples, SPRY1 expression levels were significantly lower in prostate cancer patients with PSA recurrence after surgical treatment (P = 0.0076) and JAG1 expression levels were significantly higher in Gleason sum (GS) 8–9 disease than in GS 5–6 (P = 0.0121). In summary a random population of LNCaP cells comprises a heterogeneous group of cells with different androgen‐deprivation sensitivities and potential for invasiveness. J. Cell. Biochem. 115: 1505–1515, 2014. © 2014 Wiley Periodicals, Inc.